BAI’ AL-SARF IN FOREIGN EXCHANGE: AN ANALYSIS OF MAQASID SHARIAH - Wan Norhaniza Wan Hasan (Journal of Islamic, Social, Economics and Development, 2018)
This study aims to analyse bai 'al-sarf in foreign exchange based on the maqasid alshariah. Money serves as a transactional medium accepted by the global community andlegislation. The abilities held by money cause it to be regarded as one of the daruriyyah needs.For this reason, Muslim scholars permit the practice of buying and selling currency by usingbai 'al-sarf contract. One of the most important requirement for the contract is that it must beconducted on spot. This situation creates restrictions on transactions that have to be conductedVolume: 3 Issue: 11 [June, 2018] pp. 22-35]Journal of Islamic, Social, Economics and DevelopmenteISSN: 0128-1755Journal website: www.jised.comm23in future or forward. This study analyse the above issues qualitatively by using secondary datacomprised of written materials on bai 'al-sarf contracts in currency exchange and maqasid alshariah to identify the concept in bai' al'sarf contract and to analyse the practices of bai 'alsarf for foreign exchange according to maqasid al-shariah. It is found that in fulfilling therequirements of maslahah and rejecting the greater mafsadah in maqasid al-shariah, foreignexchange may use other contracts as a hedging mechanism while still adhering to theprinciples of sharia through sharia-compliant derivative instruments such as Islamic FXforward, Islamic FX option and Islamic FX swap by using other contracts and principles thatmeet the requirements of sharia.